KOLONI SEMUT Myopopone castanea SMITH (hymenoptera : formicidae) SEBAGAI PREDATOR Oryctes Rhinoceros L. (coleoptera: scarabaidae) PADA ONGGOKAN BATANG SAWIT DI LABORATORIUM - Rini Susanti; Darma Bakti; Marheni (Jurnal Pertanian Tropik, 2017)
Ants are one potential predator of O. rhinoceros L. (Coleoptera: Scarabaidae). The purpose of this study wasto determine the ants of colony Mypoponae castanea as predators of the palm stem borer O. rhinoceros(Coleoptera: Scarabaidae) on a pile of oil palm trunk in the laboratory. This research was conducted at theLaboratory of Pest Plant of the Faculty of Agriculture, University of Sumatra Utara, Medan (± 25 m abovesea level). This research was conducted in November 2014 to Agustus 2015. The results showed a colony ofM. castanea had one queen with 5-6 male ants and 60-70 worker ants in the laboratory.